LITERASI KEUANGAN DAN PERILAKU KEUANGAN KARYAWAN SWASTA DI KABUPATEN JEPARA: Financial Literacy and Financial Behavior of Private Employees in Jepara Regency - Hadi Ismanto; Nisa Ihlasul Amaiyah (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Financial behavior is an interesting topic, given the consumptive Indonesian society. This study aims to analyze the relationship of financial literacy and demographic factors in determining the financial behavior of private employees in Jepara Regency. The sampling method uses purposive sampling and data is measured using a Likert scale 1 to 5. Data are analyzed using a quantitative approach including validity and reliability, multiple linear regression analysis, coefficient of determination, F-test, and t-test. The results of this study indicate that age, education level, income, and financial literacy simultaneously determine the financial behavior of private employees, but individually income does not affect financial behavior. High-income private employees need to control behavior in managing finances, reducing consumer spending and managing finances well. Keywords: multiple linear regression analysis, demographic factors, education, financial behavior, financial literacy